Does Social Health Insurance Reduce Financial Burden? Panel Data Evidence from India - Mehtabul Azam (Institute for the Study of Labor (IZA), 2016)
Indian government launched the Rashtriya Swasthya Bima Yojana (RSBY), a national health insurance scheme, in 2008 that provides cashless health services to poor households in India. We evaluate the impact of RSBY on RSBY beneficiary households' (average treatment impact on the treated) utilization of health services, per capita out-of-pocket (OOP) expenditure, and per patient OOP expenditures on major morbidities. To address the issue of non-randomness in enrollment into the scheme, we exploit the longitudinal aspect of a large nationally representative household survey data to implement a difference-in-difference with matching. We find some evidence of positive impact of RSBY on utilization of health services by RSBY beneficiary households in rural India but not in urban India. However, there is no evidence that the RSBY reduced per person OOP expenditure for RSBY households in both rural and urban areas. Conditional on having received medical treatment for major morbidity, we find that RSBY increased probability of hospitalization and being treated by a government doctor in rural areas but no significant impact in urban areas. We also find lower expenditure on medicine for a RSBY cardholder patient in rural areas.
Keywords: I1; I18; I38; 330; SHI; RSBY; IHDS; out-of-pocket expenditure; health services utilization